Enhanced cold tolerance mechanisms in Euglena gracilis: comparative analysis of pre-adaptation and direct low-temperature exposure - Yuan, Shuai; Fu, Wen; Du, Ming; Yao, Rao; Zhang, Dan; Li, Chao; Chen, Zixi; Wang, Jiangxin (Frontiers in Microbiology, 2024)
Microalgae, known for their adaptability to extreme environments, are important for basic research and industrial applications. Euglena, unique for its lack of a cell wall, has garnered attention due to its versatility and the presence of bioactive compounds. Despite its potential, few studies have focused on Euglena's cold adaptation mechanisms. This study investigates the cold adaptation mechanisms of Euglena gracilis, a microalga found in highly diverse environmental habitats, by comparing its growth, photosynthetic performance, and physiological and biochemical responses under two low-temperature cultivation modes: pre-adaptation to 16°C followed by exposure to 4°C (PreC) and direct exposure to 4°C (DirC). In this study, the PreC group exhibited superior growth rates, higher photosynthetic efficiency, and more excellent antioxidant activity compared to the DirC group. These advantages were attributed to higher levels of protective compounds, enhanced membrane stability, and increased unsaturated fatty acid content. The PreC group's ability to maintain higher cell vitality under cold stress conditions underscores the significance of pre-adaptation in enhancing cold tolerance. The findings from this research provide valuable insights into the mechanisms underlying cold adaptation in E. gracilis, emphasizing the benefits of pre-adaptation. These insights are crucial for optimizing the cultivation of algal species under cold stress conditions, which is essential for both biotechnological applications and ecological studies. This study not only advances our understanding of Euglena's adaptive responses to low temperatures but also contributes to the broader field of algal research and its industrial exploitation.